Acid-mediated domino reaction of ortho-carbonylated alkynyl-substituted arylaldehydes with phenols: Rapid access to fused indeno[2, 1-c]chromen-7-one derivatives. Issue 24 (15th June 2017) - Zhu, Hongbo; Cao, Ziping; Meng, Xin; Tian, Laijin; Chen, Guang; Sun, Xuejun; You, Jinmao
Abstract: Acid-mediated domino reaction of ortho -carbonylated alkynyl-substituted arylaldehydes with phenols is described. The implement of this reaction can provide directly a variety of tetracyclic indeno[2, 1- c ]chromen-7-one products in good yields. The mechanism was proposed to be a domino indanone ring formation/ortho-alkylation of phenols/dehydrated cyclization for the formation of polycyclic skeleton. In addition, several interesting dimeric products containing a pentacyclic scaffold were also afforded stereoselectively albeit in moderate yields. The present transformations feature the use of simple acid catalyst, short reaction time and good substrate scope. Graphical abstract: